A theoretical model of Polycomb/Trithorax action unites stable epigenetic memory and dynamic regulation - Jeannette Reinig; Frank Ruge; Martin Howard; Leonie Ringrose (Nature Communications, 2020)
Polycomb (PcG) and Trithorax (TrxG) group regulate several hundred target genes with important roles in development and disease. Here the authors combine experiment and theory to provide evidence that the Polycomb/Trithorax system has the potential for a rich repertoire of regulatory modes beyond simple epigenetic memory.